2016
DOI: 10.1021/acs.nanolett.6b00225
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependence of Acceptor and Donor Levels of Boron and Phosphorus Codoped Colloidal Silicon Nanocrystals

Abstract: Size dependence of the boron (B) acceptor and phosphorus (P) donor levels of silicon (Si) nanocrystals (NCs) measured from the vacuum level was obtained in a very wide size range from 1 to 9 nm in diameter by photoemission yield spectroscopy and photoluminescence spectroscopy for B and P codoped Si-NCs. In relatively large Si-NCs, both levels are within the bulk Si band gap. The levels exhibited much smaller size dependence compared to the valence band and conduction band edges. The Fermi level of B and P codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 56 publications
8
76
0
Order By: Relevance
“…The PL spectrum shifts down by 0.4 eV (from 1.45 eV down to 1.05 eV) as both boron and phosphor were doped into the sample. This has been observed before and assigned to radiative recombination of e–h pairs localized at donor and acceptor levels inside the bandgap of Si NC ; in that way emission at energies below the bandgap of bulk Si could be obtained. Concomitantly, from Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The PL spectrum shifts down by 0.4 eV (from 1.45 eV down to 1.05 eV) as both boron and phosphor were doped into the sample. This has been observed before and assigned to radiative recombination of e–h pairs localized at donor and acceptor levels inside the bandgap of Si NC ; in that way emission at energies below the bandgap of bulk Si could be obtained. Concomitantly, from Fig.…”
Section: Resultssupporting
confidence: 58%
“…For these materials, an incomplete compensation is the main origin of the low PL quantum efficiency. For co‐doped NCs, the Coulomb correction due to donor–acceptor pair interaction varies strongly with the dopant concentration; consequently the PL emission energy reduces at high doping levels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In large Si‐NCs, by engineering impurity location, co‐doping can be exploited to tune the energy of the gap from the visible range to values below the energy gap of the Si‐bulk, in agreement wth the experimental observations . Moreover, very recently Hori et al have demonstrated using photoemission yield spectroscopy and photoluminescence spectroscopy that for B and P codoped Si‐NCs with relatively large sizes both the HOMO and LUMO levels are within the band gap of bulk Si crystal, confirming that these are acceptor and donor levels, and that, with decreasing the size from 9 to 1 nm, the HOMO level becomes about 0.46 eV deep and the LUMO level about 0.47 eV shallow, in fair agreement with the theoretical outcomes …”
Section: Co‐dopingsupporting
confidence: 64%
“…It has been recently shown that doping is a critical means to realize the full potential of Si NCs [16][17][18][19]. For example, low-energy light emission related to the transitions of electrons from the band edge to the defect state has been observed in boron (B)-and phosphorus (P)-doped Si NCs [20][21][22][23], leading to enhanced tunability of the light emission from Si NCs. In addition, heavy B and P doping have enabled localized surface plasmon resonance (LSPR) for Si NCs [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%